2015
DOI: 10.1161/hypertensionaha.115.05159
|View full text |Cite
|
Sign up to set email alerts
|

Independent Associations of Circulating Galectin-3 Concentrations With Aortic Pulse Wave Velocity and Wave Reflection in a Community Sample

Abstract: Abstract-Although the profibrotic inflammatory substance galectin-3 predicts outcomes in the general population, the mechanisms responsible for this effect are uncertain. We aimed to determine whether circulating galectin-3 concentrations are associated with carotid femoral (aortic) pulse wave velocity and aortic reflective wave index (applanation tonometry and SphygmoCor software) in 966 randomly selected participants from a community sample. Galectin-3 concentrations were not independently associated with of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 26 publications
1
11
1
1
Order By: Relevance
“…In a recent study carried out in 966 randomly selected participants from a community sample, Gal‐3 concentrations were not found to be independently associated with office or, more importantly, ambulatory BP . This result is in contrast to prior study findings showing a relationship between Gal‐3 and either the hypertensive condition or office BP values.…”
contrasting
confidence: 85%
“…In a recent study carried out in 966 randomly selected participants from a community sample, Gal‐3 concentrations were not found to be independently associated with office or, more importantly, ambulatory BP . This result is in contrast to prior study findings showing a relationship between Gal‐3 and either the hypertensive condition or office BP values.…”
contrasting
confidence: 85%
“…Moreover, Gal-3 promotes the vascular calcification associated with atherosclerosis [ 15 ]. Interestingly, Gal-3 positively associated with pulse wave velocity, an index of arterial stiffness in a community sample [ 24 ]. The authors suggest that Gal-3 may contribute toward adverse cardiovascular effects in-part through an effect on aortic stiffness, effects which cannot be attributed to generalized inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…30, 31 Furthermore, arterial elasticity is impaired in patients with PAD. 32 Libhaber et al, 33 found a significant correlation between G3 and carotid-femoral pulse wave velocity, which primarily measures the arterial elasticity of the aorta, in 966 participants of African descent in South Africa. The lack of association between G3 and arterial elasticity in the current study suggests that a global measurement of DPCA fails to detect differences in predominantly large vessels like the aorta.…”
Section: Discussionmentioning
confidence: 99%